Coordinated Systemic Stomatal Responses in Soybean . Issue 4 (5th June 2020) - Zandalinas, Sara I.; Cohen, Itay Hamus; Fritschi, Felix B.; Mittler, Ron
Abstract : Rapid and coordinated systemic stomatal responses occur in the crop plant soybean and could be involved in acclimation to changes in light conditions occurring in the field as a result of sunflecks.